Analisis Pengaruh Green Marketing dan Brand Image terhadap Loyalitas Konsumen - Melisa Melisa (Universitas Bunda Mulia, 2023)
This study aims to see the effect of green marketing and brand image on consumer loyalty to the Starbucks Coffee brand partially and simultaneously, where the population in this study is Starbucks consumers in Jakarta who have bought the product before. Then the sample was taken using purposive sampling and random sampling as many as 90 respondents, and there were only 78 respondents' data that could be processed. This type of research is quantitative research with two independent variables, namely green advertising and brand image and the dependent variable is consumer loyalty. The data analysis technique used is multiple linear regression using the Jamovi program and it is known from the results of data processing that green advertising and brand image partially and simultaneously have a significant effect on consumer loyalty, whereas from the results of the study the brand image variable has a more significant influence on consumer loyalty.